An implicit simplified sphere function-based gas kinetic scheme for simulation of 3D incompressible isothermal flows. (4th January 2018) - Yang, L.M.; Shu, C.; Yang, W.M.; Wang, Y.; Lee, C.B.
Highlights: An implicit simplified SGKS is presented for simulation of 3D incompressible isothermal flows. The formulations for numerical fluxes at the cell interface can be given explicitly and concisely. The implicit LU-SGS method is introduced to further improve the computational efficiency and numerical stability. The computational efficiency of present scheme is significantly higher than that of the original SGKS and the lattice Boltzmann flux solver (LBFS). Abstract: In this work, an implicit simplified sphere function-based gas kinetic scheme (SGKS) is presented for simulation of 3D incompressible isothermal flows. At first, the numerical fluxes of governing equations are reconstructed by the local solution of Boltzmann equation with sphere function distribution. Due to incompressible limit, the sphere at cell interface can be approximately considered to be symmetric as shown in the work. Besides that, the energy equation is usually not needed for simulation of incompressible isothermal flows. With all these simplifications, the formulations of the simplified SGKS can be expressed concisely and explicitly. Secondly, the commonly-used implicit Lower-Upper Symmetric Gauss-Seidel (LU-SGS) method is adopted to further improve the computational efficiency and numerical stability of present scheme. In LU-SGS method, only a forward and a backward sweep are needed for marching the conservative variables in time. As a result, the simplified SGKS with the LU-SGS method can be implemented easily. Numerical experiments, including the 3D lid-driven cavity flow and flow over a backward-facing step, showed that the incompressible isothermal flows can be well simulated by the developed scheme and its computational efficiency is significantly higher than that of the original SGKS and the lattice Boltzmann flux solver (LBFS). In addition, it was found that the present scheme with the LU-SGS method is more efficient than that with the explicit Euler method, and the speedup ratio is about 2 to 5.